XRD, DTA AND TGA INVESTIGATIONS OF THE BaFe12-xAlxO19 SOLID SOLITIONS - Jabarov, Sakin; Trukhanov, Alex; Trukhanov, Sergey; Mammadov, Ali; Turchenko, Vitaly; Mehdiyeva, Rafiga; Huseynov, Ramiz (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
By X-ray diffraction, differential thermal analysis (DTA) and thermo-gravimetric analysis (TGA) were investigated BaFe12-xAlxO19 hexaferrites with various concentrations of Al (x = 0.3, 0.9 and 1.2). Crystal structure of compounds was determined, and it determined that under normal condition (P = 0 GPa, T = 300 K) they possess structure is hexagonal symmetry with the space group P63/mmc. Replacing Fe3+ ions Al3+ with ions, on account of reducing ion radius, decrease of indices of parameters was occurred. This crystal structure is saved in a temperature range 30 - 950 ÂºC and structural phase transition do not occur. Energy supplied to a system is fully swallowed by a system, monotonic decrease is occurred in TGA curve and in DTA curve endo and exo effects do not occur.